Identifying Factors of Female Students’ Behavioral Intention to use 5G for Online Education in Sichuan, China - Xi, Wang (Scholar: Human Sciences, 2024)
Purpose: The rapid development of higher education in China realizes the importance of 5G in smart education. Hence, this study examines the factors that influence the behavioral intention of female students in Sichuan universities to use the 5G for online education platform. Seven variables and eight hypotheses are constructed regarding previous research, including perceived ease of use, system quality, information quality, service quality, attitude, social influence, perceived usefulness and behavioral intention. Research design, data, and methodology: The quantitative study was conducted by distributing a questionnaire to 560 female university students from three universities in Sichuan. Confirmatory factor analysis and structural equation model were applied for data analysis and results. Results: The results showed that attitude was the strongest predictor of behavioral change he strongest predictor of behavioral intention to use followed by social influence and perceived usefulness. Compared to perceived usefulness, the perceived ease of use had the strongest effect on attitude. Conclusions: The findings of this paper contribute to better understanding of 5G for online education developers, marketers, senior managers in higher education institutions, or related practitioners. Therefore, choice and use and ease of use at university would increase positive feedback and enable students to use the platform system for ongoing learning.